Which One is Better? Jigsaw II Versus Jigsaw IV on the Subject of the Building Blocks of Matter and Atom - Hakan Turkmen; Didem Buyukaltay (Journal of Education in Science, Environment and Health)
In this study, the effect of using Jigsaw II and Jigsaw IV techniques on the subject of “Atoms-The Basic Unit of Matter” in science course of 6th grade on academic achievement was examined. Pre-test post-test control group research was used in the study. Study population is all secondary schools in Turgutlu district of Manisa province and the sample group was determined from “Samiye Nuri Sevil Secondary School” among 20 secondary schools in Turgutlu district through cluster sampling method. The experiment and control groups of the research were constituted from two branches based on the results of pre-test and there are 48 persons in total of which 24 are in experiment and 24 are in control group. In the study, the subject of “Atoms- the Basic Unit of Matter” was taught to the experiment group by using Jigsaw IV technique and it was taught to the control group by using Jigsaw II technique.  In this research, Science achievement test consisting of 12 multiple-choice items which were developed by the researcher was used. T-test was used for the analysis of data obtained as a result of achievement test. In paired samples t-test (dependent group) conducted for achievement pre-tests and post-tests of the control and experiment group a significant difference was found, while no significant difference in terms of statistics in favor of the experiment group was found in independent samples t-test (independent group) conducted for post-tests of the control and experiment groups. At the end of the research, although the effect of Jigsaw II and Jigsaw IV techniques on the achievement in Science course was found to be positive on students learning, no statistical differences were found in these two techniques.